(untitled) (Indian Journal of Animal Production and Management, 2013)
A study was conducted to know about the managemental practices, housing pattern and economy of samll-scale broiler farming in-and-around Livestock Research Station, AAU, Mondira under Kamrup district of Assam in half a dozen villages on 60 number of broiler farms, six from each village. It was observed that most of the broiler sheds were of temporary type with east west direction, located by the side of dweling houses. Broiler houses were constructed with locally available materials like thatch, bamboo and wood with asbestos/GI sheet as roofing material. The available floor space and air space provided to each broiler were 1.00 to 1.25 sw. ft. and 6-9 cu.ft. respectively. Small-scale broiler units of 200-500 numbers per bacth were found to be common. Almost all farmers did not use brooders but5 used kerosene and had kutcha floor (not concrete). All the farmers used standard compounded broiler feeds but did not get facilities for post mortem examination of their dead birds. The market age of broilers was 5 weeks and average market weight was above 2.00 kg. The available price of live broiler was Rs. 60-70 per Kg. Average mortality rate from day-old stage to market age was 10-12%.